Prof Hopkins tidsresa tillbaka till kristendomens födelse: Keith Hopkins, A World Full of Gods: Pagans, Jews and Christians in the Roman Empire. London:Weidenfeld & Nicolson 1999. - Rydbeck, Lars (AIGIS, 2024)
Intet.